Evidence of Validity of the Perceived Self-Efficacy for Academic Situations Scale: A Psychometric Network Analysis - Ventura-León, José (2025)
Introduction: Related to psychological well-being and resilience, self-efficacy is a key determinant of academic performance. Objective: To assess the validity and reliability of the Perceived Self-Efficacy for Academic Situations Scale in a Peruvian university sample using psychometric network models. Method: A total of 600 participants took part, with a mean age of 25.49 years (SD = 7.82), 67.3% of whom were women. Dimensionality, structural consistency, and network loadings were evaluated using Exploratory Graph Analysis (EGA). In addition, the relationship between academic satisfaction and self-efficacy was examined. Results: The scale showed a unidimensional structure with ideal structural consistency (SC = 1.00). Network loadings ranged from moderate to high (0.26 to 0.39), and invariance between sexes was found. Academic self-efficacy and satisfaction had a moderate correlation (r = .50). Discussion and Conclusions: The results support the scale’s validity and reliability, highlighting its usefulness in educational settings. Further research with diverse samples is encouraged.